(untitled) (European Journal of Marketing and Economics, 2024)
This study introduces some new perspectives of bureaucratic corruption into the dynamic general equilibrium theory recently proposed by Zhang. The main concern of our study is the role of corruption on economic growth and income and wealth distribution between the officials and workers. The economy is composed of the industrial sector and public sector. The population is classified into officials and workers. Corruption takes places through many channels. Officials take brides from producers and households. The model describes dynamic interactions of growth, corruption with fixed tax rate and corruption rates. We simulate the model to demonstrate existence of equilibrium and motion of the dynamic system. We also examine effects of changes in different parameters on the motion of the economic system.